Troponin Elevation and Myocardial Injury in Patients Admitted to an Internal Medicine Department: Diagnostic and Prognostic Significance - Carrington,Mafalda (2020)
Introduction: An elevated troponin is often found in patients admitted to the hospital. The meaning and the classifications of patients with this elevation (myocardial injury, either acute or chronic, versus acute myocardial infarction, either type 1 or type 2) remains unclear. The aim of our study was to assess the meaning and to classify the patients admitted to an internal medicine department with an elevated troponin level. Material and Methods: A clinical retrospective analysis of hospitalized patients admitted to an internal medicine department was conducted over a 2-year period. We identified patients with at least 2 troponin I measurements, and at least 1 above 0.1 ng/mL. Population was characterized according to demographics, cardiovascular risk factors, clinical presentation, treatment and prognosis. Troponin elevation was interpreted according to the fourth universal definition of myocardial infarction. Results: A total of 90 patients were enrolled, with a mean age of 83 years ((± 8.1), 52% were male. Sixty patients (66%) had myocardial infarction criteria, and the remaining 30 patients (33%) were classified as acute myocardial injury, without infarction. We found no clinical difference between these patients, except for age, which was higher in myocardial infarction patients (84 ± 7 vs 81 ± 10 years, p = 0.039). Patients had a high disability score (43% had an ECOG 3 or 4), hypertension (89%), heart failure (51%), type 2 diabetes (50%), chronic kidney failure(35%), atrial fibrilation or flutter (35%) and had had a previous myocardial infarction (33%). Clinical presentation included dyspnea (44%) and chest pain (13%). On discharge, patients were prescribed a statin (64%) and antiplatelets (58%). In-hospital mortality was 17%, while 30 days and 1 year mortality were 27% and 51% respectively. Conclusion: In this study, in a real-world cohort of patients admitted to an Internal Medicine department over a 2-year period, troponin levels were analyzed in 9%, and acute myocardial injury was found in one third of those patients. These patients had criteria for acute myocardial infarction in 66% and of acute myocardial injury without infarction in 33%. Age was higher in myocardial infarction patients, whilst there were no differences in other clinical, management or prognostic features. Patients were elderly and fragile, with a higher prevalence of several comorbidities, when compared with studies based on Cardiology departments. Mortality was high, with half the patients dying within a year, even with the prescription of statins in 64% and antiplatelets in 60%.